2022
DOI: 10.1684/epd.2021.1403
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of a competing endogenous RNA network associated with circRNAs dysregulated in medial temporal lobe epilepsy

Abstract: Objective. The aetiology and pathogenesis of medial temporal lobe epilepsy (MTLE) remain unclear, and effective treatments are lacking. The involvement of a dysregulated competing endogenous RNA (ceRNA) network in MTLE is only partially understood. The purpose of this study was to investigate MTLE regulatory networks composed of messenger RNAs (mRNAs), circular RNAs (circRNAs), long non-coding RNAs (lncRNAs), and microRNAs (miRNAs) through a ceRNA network map. Methods. RNA sequencing (RNA-seq) and small RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Via bioinformatics technology, researchers used Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) network to reveal that synapses play a crucial role in medial temporal lobe epilepsy (MTLE) [ 23 ]. It has been reported that the changes of postsynaptic glutamate receptor increase the excitability of hippocampal neural network, and 4-aminopyridine (4-AP) -induced epileptiform activity in hippocampal brain slices of rat in vitro model shows that alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA)/N-methyl-D-aspartate (NMDA) ratio increases [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Via bioinformatics technology, researchers used Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) network to reveal that synapses play a crucial role in medial temporal lobe epilepsy (MTLE) [ 23 ]. It has been reported that the changes of postsynaptic glutamate receptor increase the excitability of hippocampal neural network, and 4-aminopyridine (4-AP) -induced epileptiform activity in hippocampal brain slices of rat in vitro model shows that alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA)/N-methyl-D-aspartate (NMDA) ratio increases [ 24 ].…”
Section: Introductionmentioning
confidence: 99%